Buddy Needle Technique to Facilitate Retrograde Puncture of Heavily Calcified Tibial Vessels. (August 2017) - Mikelarena, Ederi; Ysa, August; Lobato, Marta; Arruabarrena, Amaia; Metcalfe, Matthew; Fonseca, Juan L.
Purpose: To describe a technical trick to overcome a prior failed retrograde puncture of the tibial vessels secondary to arterial calcification.Technique: Following a prior failed retrograde puncture attempt, the needle is left in place next to the artery. The tip of the needle is then moved toward the artery as a lever so that the artery is fixed between the needle, the skin, and the surrounding tissues. With the artery fixed, a standard puncture procedure is performed. Alternatively, if additional support is needed, 2 micropuncture needles are inserted one on either side of the artery, crossing under the target vessel and hence trapping it between them, providing additional support and therefore enhancing the chance of successful arterial access.Conclusion: The buddy needle technique may be considered as an alternative procedure in a retrograde pedal/tibial approach after prior failed standard attempts in patients with heavily calcified vessels.